Web-Based Zakat Information and Calculation System at Badan Amil Zakat Nasional (BAZNAS) of the Kendari City Using the Laravel Framework - Hafizh Pratama; Aprilia Kurnianti; Asep Setiawan (Emerging Information Science and Technology, 2022)
Badan Amil Zakat Nasional (BAZNAS), or the National Amil Zakat Agency, is housed in Kendari City, particularly in the Anduonohu area. BAZNAS is a non-structural government institution independent and responsible to the Ministry of Religious Affairs. It faces several issues with data processing using Microsoft Excel, such as the difficulty of zakat data administration, the time and effort required to create reports, the slowness of search results, and the absence of a database. By developing a web-based zakat information and calculation system at BAZNAS of Kendari City with the Laravel framework, this study aims to discover solutions to issues experienced. The research framework for addressing the issues raised at BAZNAS of Kendari City included problem identification, theoretical foundation-based information searches, data collection through observation and interviews, and application development. Prototyping was utilized as a part of the system development, employing PHP, the Laravel framework and a MySQL database. Black-box testing was applied to ensure everything was working as intended. The test findings unveiled that the web-based zakat information and calculation system at BAZNAS of Kendari City functioned properly.